Malignome als Ursache von chronischen Wunden - Siegling, Michael; Erfurt-Berge, Cornelia (Chirurgische Praxis, 2023)
The differentiation between primary and secondary malignant wounds is often complicated. Primary tumours of the skin such as basal cell carcinoma, squamous cell carcinoma, malignant melanoma, cutaneous lymphoma and sarcoma alike cutaneous metastasis can ulcerate and ultimately manifest as malignant wounds. Similarly, initially tumour-free chronic wounds can transform into secondary malignancies via malignant transformation. A correct and timely diagnosis is essential and forms the basis of the subsequent curative or palliative therapy. In the context of wound management of chronic and palliative wounds, disease-oriented treatment and the patients‘wishes should go hand in hand. In order to fulfil the holistic empathic approach of wound care, high importance should be attached to psychological aspects, prevention of off odours, exudate management, wound rinse and wound cleansing as well as to an individual pain therapy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: chronic wounds; malignant transformation; malignant wounds; tumours; wound management